2018
DOI: 10.20937/rica.2018.34.02.02
|View full text |Cite
|
Sign up to set email alerts
|

BACTERIAL COMMUNITIES OF THE OYSTERS Crassostrea corteziensis AND C. sikamea OF COSPITA BAY, SINALOA, MEXICO

Abstract: This work aimed to quantify the bacterial loads and determine the taxonomic composition of the microbial communities of oysters Crassostrea corteziensis and C. sikamea, as well as the surrounding waters of Cospita Bay, using two sets of samples (M1 and M4) obtained in the dry season and two (M2 and M3) in the rainy season. Bacterial loads were quantified with the viable count technique and out of the 320 strains isolated for their different morphologies, 84 were identified with molecular techniques to the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Bacterial infections have been little studied in the subtropical and tropical oysters of the American Pacific, and, although there is a relationship of bacterial infection when oysters are infected with the OsHV-1 virus (C´aceres-Mart´ınez & V´azquez-Yeomans 2013), there are no specific studies that can determine the type of these infections. Luis-Villasen˜or et al (2018) conducted a study on the communities of the oysters Crassostrea corteziensis and Crassostrea sikamea from commercial oyster farms in Mexico. They found that the Kumamoto oyster C. sikamea presented a greater diversity of species and the highest number of pathogenic bacteria for aquatic organisms, which is a probable reflection of their poor health status in tropical culture.…”
Section: Diseasesmentioning
confidence: 99%
“…Bacterial infections have been little studied in the subtropical and tropical oysters of the American Pacific, and, although there is a relationship of bacterial infection when oysters are infected with the OsHV-1 virus (C´aceres-Mart´ınez & V´azquez-Yeomans 2013), there are no specific studies that can determine the type of these infections. Luis-Villasen˜or et al (2018) conducted a study on the communities of the oysters Crassostrea corteziensis and Crassostrea sikamea from commercial oyster farms in Mexico. They found that the Kumamoto oyster C. sikamea presented a greater diversity of species and the highest number of pathogenic bacteria for aquatic organisms, which is a probable reflection of their poor health status in tropical culture.…”
Section: Diseasesmentioning
confidence: 99%